New Mexico curiosities : quirky characters, roadside oddities & other offbeat stuff - Lowe, Sam (Guilford, Conn. : Globe Pequot Press, 2009)
Whether you?re a born-and-raised New Mexican, a recent transplant, or just passing through, New Mexico Curiosities will have you laughing out loud as it introduces you to the most fascinating characters in the Spanish State, and takes you places you never could have imagined?some of them right around the corner!--Amazon.com.
Keywords: Curiosities and wonders -- New Mexico; Miscellanea; New Mexico